Efficacy of Indocyanine Green Fluorescence Angiography in Preventing Anastomotic Leakage After McKeown Minimally Invasive Esophagectomy - Luo, Rao-Jun; Zhu, Zi-Yi; He, Zheng-Fu; Xu, Yong; Wang, Yun-Zheng; Chen, Ping (Frontiers in Oncology, 2021)
Background: Indocyanine green (ICG) fluorescence angiography (FA) was introduced to provide the real-time intraoperative evaluation of the vascular perfusion of gastric conduit during esophagectomy. However, its efficacy has not been proven. The aim of the study is to assess the usefulness of ICG-FA in the reduction of anastomotic leakage (AL) rates in McKeown minimally invasive esophagectomy (McKeown MIE). Methods: From June 2017 to December 2019, patients aged 18–80 years with esophageal carcinoma were enrolled in the study and all underwent McKeown MIE. Patients were divided into two groups: with or without ICG-FA. Patients' demographics and perioperative outcomes were comparable between the two groups. The primary outcome was the rate of AL. Results: A total of 192 patients were included: 86 in the ICG-FA group and 106 patients in the no-ICG-FA group. There were 12 ALs (6.3%) overall. The rate of AL was 10.4% in the no-ICG-FA group, which was significantly higher than the 1.2% in the ICG-FA group. Conclusions: ICG fluorescence angiography has the potential to reduce the rate of anastomotic leakage in McKeown minimally invasive esophagectomy.